Histologie - Wolf, Jan; Stanek, Ivan, 1915-1972; Hegar, Milan; Macek, Zdeněk, 1913-; Neubert, Oldřich (Praha : Státní zdravotnické nakladatelství, 1966)
Obsahuje anotáciu na obale
Obsahuje register
Keywords: histológia -- príručky